Analisis Sistem Kemitraan Petani Tembakau dengan PT Sadhana Arifnusa: Studi Kualitatif tentang Tingkat Kepuasan Bermitra di Kabupaten Nganjuk - Aulia, Kunti Rachma; Sumarji, Sumarji; Daroini, Ahsin (Universitas Islam Kadiri, 2025)
Partnerships between farmers and companies are a strategic policy in the development of the agricultural sector in Indonesia, including tobacco, which is a high-value commodity but vulnerable to price fluctuations and production risks. This study aims to describe the partnership system between PT Sadhana Arifnusa and tobacco farmers in Nganjuk Regency and to analyze the influence of this partnership on farmers' risk preferences and satisfaction. The research was conducted using a qualitative descriptive method in Ngluyu and Gondang sub-districts. The results indicate that the partnership system includes the provision of production inputs, technical guidance, and market guarantees by the company, while farmers are required to follow cultivation standards and sell their entire harvest to the company. The partnership provides tangible benefits to farmers in the form of increased income, price certainty, and reduced farming risks. For the company, the partnership ensures a continuous supply and quality of tobacco according to established standards. This partnership model proves to be an effective strategy for mitigating production and market risks in tobacco farming in Nganjuk Regency